Linking design problems and modular solutions. (2019) - Fiorineschi, Lorenzo; Rotini, Federico
Designing products implies to deal with a series of issues affecting their entire life cycle, which are often solved by exploiting the benefits offered by modular architectures. Nevertheless, although several studies have been performed on this argument, understanding 'when' and 'how' to adopt modularity still remains a non-trivial task, especially in the early design stages. Indeed, different modularity types can be found in literature, but it is unclear whether they can be linked to specific categories of design problems or not. Attempting to fill this gap, the paper proposes an investigation strategy to highlight the relationship between modular solutions and design problems. An illustrative application of the proposal on a sample of products is presented together with the achieved results. They show that the proposed investigation approach potentially allows to highlight preferred modular solutions for specific problem categories. Moreover, a new set of unambiguous definitions of the modularity types is presented to clearly identify interfaces and interactions among modules.